Deskripsi Singkat Revisi Taksonomi Bloom - Rukmini, Elisabeth (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The Bloom’s taxonomy revision mainly consisted of curriculum,instructional design, and assessment. Educational development, socioculturalchanges, researches in neurosciences and educationalpsychology are the major influences those supported the revision.Civitas academia may find that the Revised Bloom’s Taxonomy is veryhelpful in its application. The users would find technical and moreapplied instructions, including some examples. This article waswritten to describe briefly of the Revised Bloom’s Taxonomy as astepping point in considering its further application.